Trends in the Emergence of Eco-Enlightenment in Higher Education Institutions in the Republic of Karakalpakstan - Khusnetdinov Ulugbek Imametdinovich (Researchparks Publishing, 2022)
In the article, the trends of eco-enlightenment in higher educational institutions in the Republic of Karakalpakstan. Based on the ethno-ecological traditions of the Karakalpaks, the chronology of the development of ecological enlightenment and culture and the main trends of the mythological views on ecological education in the earliest times are highlighted.